Using a Community Preventive Services Task Force Recommendation to Prevent and Reduce Intimate Partner Violence and Sexual Violence - Okasako-Schmucker, Devon L. (J Womens Health (Larchmt), 2019)
Intimate partner violence (IPV) and sexual violence (SV) are preventable public health problems affecting millions in the United States. The Community Preventive Services Task Force (CPSTF), an independent panel of experts that develops evidence-based recommendations based on rigorous systematic reviews, recommends interventions that aim to prevent or reduce IPV and SV among youth aged 12–24 years. Decision makers can use these findings to select interventions appropriate for their populations, identify additional areas for research, and justify funding requests.